Analisis Hasil Riset Penerapan Model Pembelajaran Inkuiri untuk Meningkatkan Keterampilan Proses Sains - Idham, Aty Zahar; Sunarti, Titin (Universitas Negeri Surabaya, 2024)
This study aims to analyze the results of research on the application of inquiry learning models to improve science process skills. Secondary data were collected through Publish or Perish (PoP) from 2017 to 2023 on Google Scholar. Data analysis uses descriptive quantitative which contains a description of the findings in the study. The results of the analysis of 23 previous research journal articles concluded that the guided inquiry learning model is an inquiry learning model that is widely used to improve science process skills. The type of research that is widely used is Quasi-Experimental (43.48%.). Learning media in the form of PhET (50.00%) is widely used in the learning process to understand and master the material. Subjective (essay) and Objective (multiple choice) assessment forms can be used to measure science process skills. The physics materials used were elasticity, static fluid, light waves, harmonic motion, vibrations and waves, harmonic vibrations, Archimedes' law, Bernoulli's law, Newton's law of motion, the zero law of thermodynamics, the balance of rigid bodies, dynamic electricity, temperature and heat, and effort and energy. The highest N-gain result is in dynamic electricity material with a value of 0.82 while the lowest N-gain is in the material of the balance of a rigid body with a value of 0.36. Keywords: inquiry learning model, science process skills